Growth Inhibitory Activity of Selected High Antioxidant Australian Syzygium Species Against the Food Poisoning and Tissue Necrotic Pathogen Clostridium perfringens - Wright, Mitchell Henry; Lee, Cameron Jay; Pollock, Charmaine Estelle; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Clostridium perfringens is a gram positive pathogen which is an etiological agent in Clostridial myonecrosis and enteritis necroticans. Unless promptly treated, C. perfringens infections may result in tissue necrosis and death. Syzygium australe (brush cherry) and Syzygium lu- ehmannii (riberry) fruit and leaves have documented therapeutic proper- ties as general antiseptic agents against an extensive panel of bacteria. Despite this, studies are yet to test the growth inhibitory activity of these species against C. perfringens. Methods: S. australe and S. luehmannii fruit and leaf extracts were investigated by disc diffusion assay for growth inhibitory activity against a clinical strain of Clostridium perfringens. Their MIC values were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Methanolic and aqueous S. australe and S. luehmannii fruit and leaf extracts as well as the corresponding fruit ethyl acetate extracts, displayed growth inhibitory activity in the disc diffusion assay against C. perfringens. The aqueous and methanolic extracts were particularly potent growth inhibitors, each with MIC values substantially <500 µg/mL. The S. australe fruit extracts were nontoxic in the Artemia franciscana bioassay (LC50 values <1000 µg/mL). All ethyl acetate extracts were also nontoxic. In contrast, the S. luehmannii aqueous and methanolic extracts (fruit and leaf), as well as the S. australe leaf extracts displayed substantial toxicity in the assay. Conclusion: The potent growth inhibitory bioactivity of the fruit and leaf aqueous and methanolic Syzygium spp. extracts against C. perfringens indicates their potential as medicinal agents in the treatment and prevention of clostridial myonecrosis and enteritis necroticans.
Keywords: Syzygium australe; Syzygium luehmannii; Riberry; Brush cher- ry; antioxidant; Myonecrosis; Enteritis necroticans; Gas gangrene.